Associative Bacteria and Arbuscular Mycorrhizal Fungus Increase Drought Tolerance in Maize (Zea mays L.) through Morphoanatomical, Physiological, and Biochemical Changes - Angélica Nunes Tiepo; Mateus Henrique Fávaro; Talita Silveira Amador; Leonardo Fernandes Tavares; Mariana Fernandes Hertel; Anderson Kikuchi Calzavara; André Luiz Martinez de Oliveira; Halley Caixeta Oliveira; Jaqueline Dias-Pereira; Hugo Humberto de Araújo; Edmilson Bianchini; José Antonio Pimenta; et al. (Plants, 2024)
Water deficiency has been recognized as a major abiotic stress that causes losses in maize crops around the world. The maize crop is very important due to the range of products that are derived from this plant. A potential way to reduce the damages caused by water deficiency in maize crops is through the association with plant growth-promoting bacteria (PGPB) and arbuscular mycorrhizal fungi (AMF). To define the mechanisms developed by associative PGPB and AMF in maize that are involved in protection against moderate drought (MD), this study evaluated the biometrical, anatomical, biochemical, and physiological parameters of maize grown under MD and inoculated with different PGPB (Azospirillum brasilense strain Ab-V5 and Bacillus sp. strain ZK) and with AMF. The relative water content did not change in the treatments. The association with ZK increased the shoot:total ratio, total dry weight, maximum quantum yield of photosystem II, vascular cylinder thickness, and vascular cylinder area. The Ab-V5 inoculation led to an increment in root dry weight, the area of metaxylem vessel elements, and nitrate reductase activity. The AMF association did not lead to changes in the measured parameters. The results indicate that the association with PGPB is a relevant alternative to contribute to reducing losses in maize crops under drought. However, AMF is not indicated for this crop under drought.